ROLE OF INFRASTRUCTURE TO DEVELOP SMALL BUSINESS AND ENTREPRENEURSHIP ACTIVITIES IN UZBEKISTAN - Narkuziyev Anvar Rustamovich (Journals Park Publishing, 2022)
Obviously, the state has a significant influence on the infrastructure supporting small and medium-sized businesses, and the state serves as the basis of this influence. Proposed laws, programs, and ordinances are currently being developed to coordinate and govern how the components of infrastructure development agencies operate. However, infrastructure development projects in the regions are managed by legislative bodies, and executive bodies are directly or indirectly involved in the implementation of state policy in the field of SME development, which has the right to consider them as infrastructure institutions.
Keywords: economic development, SME, infrastructure, resource potential, region, soft infrastructure, hard infrastructure.